TEACHERS’ BELIEF TOWARDS CORRECTIVE FEEDBACK IN TEACHING WRITING DURING COVID-19 PANDEMIC - Widodo Widayanto; Haris Dibdyaningsih; Ahmad Syafi’I (Journal of English Language Teaching and Islamic Integration, 2023)
Writing is the most difficult skill in English, because it has complex process inside. There is a way that usually teachers do to help students in solving theirs writing difficulties, that is giving feedback. The problem is that, is all of the teachers use feedback while teaching writing and are they consider the importance of giving feedback, especially in this pandemic situation? By looking at this issue the researcher wants to know teachers’ point of view in giving corrective feedback to the student through teachers’ beliefs.